Diseño de un Metodo Heurístico para Secuenciación en Sistemas Flow Shop Estrictos con Buffers Ilimitados - Salamanca L, Diana Catherine; Ortiz Cabuya, Harry Andrés; López Bello, César Amilcar (Ingeniería, 2008)
This article proposes a heuristic method for solve the problem of sequencing for systems with Strong Flow Shop Buffer Unlimited, with an objective function that is the minimization the processing time of the last order in the system, the makespan. The solution to the problem was based on the creation of an approximation method or procedure heuristic, which has two phases: the first where he gets an initial sequence through a heuristic constructive, and the second phase which applies a Heuristic improvement taking as a basis the response found in the earlier stage, and through a series of iterations, generated responses alternate, within which they choose the best sequence. By using the proposed method, we obtained better answers regarding the rules FIFO LPT, SPT and the Palmer Heuristic Method route to the goal, in the indicators Makespan, flow time, average flow time, rate of use of machine, percentage dead-time machine, total waiting time and average waiting time.